OPTIMALISASI PELIBATAN MASYARAKAT LOKAL DALAM PENGEMBANGAN DESA WISATA COMPANG TODO KABUPATEN MANGGARAI (Jurnal Destinasi Pariwisata, 2026)
Compang Todo Tourism Village is one of the tourist destinations located in Manggarai Regency, East Nusa Tenggara Province. This village is recognized as a cultural tourism destination that is closely tied to local wisdom and possesses distinctive features that serve as unique tourist attractions. However, the involvement of the local community in the development and management of tourism attractions in the village remains suboptimal, thereby hindering efforts to achieve sustainable tourism development. This study aims to examine the level of community participation in the development of tourist attractions in Compang Todo Tourism Village and to formulate strategies for optimizing their involvement. A qualitative descriptive approach was employed in this research, with data collection methods including in-depth interviews, direct observation, literature review, and documentation. Informants were selected using purposive sampling. Data analysis was conducted using the SOAR (Strengths, Opportunities, Aspirations, Results) framework to identify internal and external factors influencing community participation in the development of Compang Todo Tourism Village.           The results indicate that the level of community participation, based on Cohen and Uphoff’s (1977) classification, remains limited at the implementation stage, particularly in the execution of tourism attractions based on the village's traditional weaving potential. Based on the SOAR analysis, ten development strategies were formulated: community empowerment and participation, development of traditional weaving attractions, training and mentoring for local residents, creation of tourism packages, development of cultural performances, strengthening of the creative economy, sustainable tourism management, improvement of tourism facilities, promotion of community-based tourism, and enhancement of marketing and promotional efforts for Compang Todo's tourism attractions. These findings highlight the importance of an inclusive and participatory approach in realizing sustainable, community-oriented tourism development.